2022
DOI: 10.3390/cells11172656
|View full text |Cite
|
Sign up to set email alerts
|

The CaMKII/MLC1 Axis Confers Ca2+-Dependence to Volume-Regulated Anion Channels (VRAC) in Astrocytes

Abstract: Astrocytes, the main glial cells of the central nervous system, play a key role in brain volume control due to their intimate contacts with cerebral blood vessels and the expression of a distinctive equipment of proteins involved in solute/water transport. Among these is MLC1, a protein highly expressed in perivascular astrocytes and whose mutations cause megalencephalic leukoencephalopathy with subcortical cysts (MLC), an incurable leukodystrophy characterized by macrocephaly, chronic brain edema, cysts, myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In fact, calcium-binding was another gene ontology term identified by both methods and many of the target proteins have a direct role in calcium homeostasis in the brain. For example, calcium levels are buffered by calbindin-1 ( calb1 ) and the membrane protein MLC1 ( mlc1 ) . Both necab2 and wolframin ( wfs1) are sensors of calcium and have a role in the synaptic release. , Anxa1 is a calcium reservoir and CaMKK2, a calcium/calmodulin-dependent protein kinase, has a possible role in neurite growth .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, calcium-binding was another gene ontology term identified by both methods and many of the target proteins have a direct role in calcium homeostasis in the brain. For example, calcium levels are buffered by calbindin-1 ( calb1 ) and the membrane protein MLC1 ( mlc1 ) . Both necab2 and wolframin ( wfs1) are sensors of calcium and have a role in the synaptic release. , Anxa1 is a calcium reservoir and CaMKK2, a calcium/calmodulin-dependent protein kinase, has a possible role in neurite growth .…”
Section: Resultsmentioning
confidence: 99%
“…For example, calcium levels are buffered by calbindin-1 (calb1) 55 and the membrane protein MLC1 (mlc1). 56 Both necab2 and wolframin (wfs1) are sensors of calcium and have a role in the synaptic release. 57,58 Anxa1 is a calcium reservoir 59 and CaMKK2, a calcium/ calmodulin-dependent protein kinase, has a possible role in neurite growth.…”
Section: Biological Relevancy Of the Generated Target Listsmentioning
confidence: 99%
“…Many signaling cascades and cellular properties are known to modulate VRAC functioning in different cell types (for review see (Jentsch, 2016)). A recent study has suggested that intracellular calcium might be an intermediate (Brignone et al, 2022), through CaMKII-mediated phosphorylation of MLC1. AQP4 forms a complex with TRPV4 and together these proteins affect RVD through a Frontiers in Genetics frontiersin.org functional interaction with VRAC (Benfenati et al, 2011).…”
Section: The Functional Role Of Mlc1 Glialcam Gprc5b and Aqp4 In Mlcmentioning
confidence: 99%
“…In several cell systems, exposure to hypotonic stimuli triggers a rise in intracellular Ca 2+ concentration, as the result of both Ca 2+ influx from extracellular space through MSCs [ 8 , 15 , 19 , 83 , 86 , 96 , 124 , 161 ] and its release from internal stores [ 99 , 127 , 149 ]. Despite the ubiquity of cytosolic Ca 2+ transients evoked by hypotonic cell swelling, intracellular Ca 2+ signals are not always needed for the RVD response.…”
Section: Introductionmentioning
confidence: 99%